CICERO, ON LIFE AND DEATH, TRANSL. JOHN DAVIE, ED. MIRIAM T. GRIFFIN, OXFORD WORLD’S CLASSICS, OXFORD UNIVERSITY PRESS, 2017 - Oana Corina Filip (Journal of Ancient History and Archaeology)
Cicero, On Life and Death, transl. John Davie, ed. Miriam T. Griffin, Oxford World’s Classics, Oxford University Press, 2017, ISBN: 978-0-19-964414-8, 260 pages.